2018
DOI: 10.4103/jispcd.jispcd_94_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dental fluorosis on the quality of life of female high school and precollege students of high fluoride-concentrated area

Abstract: Aims and Objectives:Colored and deformed fluorotic teeth may affect the quality of life (QOL). The present study, therefore, evaluates the effect of dental fluorosis on the QOL of female high school and precollege students of Behbahan district in 2014.Materials and Methods:One hundred 15–18-year-old female students with dental fluorosis were selected from the high schools of Behbahan district by random cluster sampling technique. Dental fluorosis was measured clinically using Dean's index after analyzing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…It was reported that higher severity of dental fluorosis was associated with lower quality of life in children. 25 Further research involving qualitative approaches, such as focus groups or interviews, would allow for a deeper understanding of children's experiences of the management of visible dental fluorosis in both general dental practice and specialist settings. It is becoming increasingly important that treatments are justified in terms of patient benefit.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that higher severity of dental fluorosis was associated with lower quality of life in children. 25 Further research involving qualitative approaches, such as focus groups or interviews, would allow for a deeper understanding of children's experiences of the management of visible dental fluorosis in both general dental practice and specialist settings. It is becoming increasingly important that treatments are justified in terms of patient benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding appropriate oral hygiene habits, one of the most important to maintain oral health is tooth brushing plus toothpaste; however, it could be the most determinant cause of the presence of fluorosis (26), as detected in the study, especially considering the fact that children started brushing their teeth with fluoride toothpaste for adults. 1450 mg / L of fluoride (27), with unmonitored and unregulated amount of toothpaste (11,23), is reflected in the correlation value of 0.162 detected, especially when considering that toothpastes marketed in the Ecuador have a percentage of fluorine that exceeds 1000 ppm which is beneficial from the preventive and protective point of view; however, it would be worth analyzing the amount used to confirm this association with the fluorosis detected.…”
Section: Discussionmentioning
confidence: 99%
“…Health organizations worldwide recommend the use of fluoridated salt in countries where water with fluoride is not very effective, considering the cost that this process represents (10). In addition, fluorides are found in table salt and, in a natural way, in different types of aliments (11); for example: in drinking water, juices, soft drinks, tea (12), toothpaste and mouthwashes (13), in which the fluoride concentration varies from 500 to 1500 mg/L (14). Different health agencies worldwide recommend the use of gels and varnishes, in a professional manner (15).…”
Section: Introductionmentioning
confidence: 99%
“…An aesthetic appearance of the teeth is the key to a beautiful smile and something valued by people of all ages and genders. Aesthetic problems could have a negative impact on a patient's psychology, limiting their social life [20][21][22]25 .…”
Section: Discussionmentioning
confidence: 99%
“…The discoloured and porous enamel of fluorosed teeth can be aesthetically unsatisfactory, impacting on patient's psychological state of mind [20][21][22] . It has been proposed that the repercussions resulting from the excessive intake of fluoride on soft tissues of children are reversible, on condition that there is a cessation of fluoride intake and the patients consume supplementary calcium, vitamin D3, ascorbic acid and antioxidants 23,24 .…”
Section: Introductionmentioning
confidence: 99%